The Social Health Status of Students at the Faculty of Psychology and Educational Sciences, Kabul University - Wafayar, Zalmay Wafayar; Sediqi, Abdul Mobin (Journal of Social Sciences - Kabul University, 2025)
This study aimed to assess social health and its dimensions among students of the Faculty of Psychology and Educational Sciences at Kabul University. A descriptive-survey design was employed and, using Cochran’s formula, a sample of 176 students was drawn from a population of 323. Data were collected via the Social Health Questionnaire developed by Saffariania (1393), which was constructed based on the theoretical model of Keyes and Shapiro, and were analyzed using SPSS version 26. An independent-samples t-test revealed that the status of students’ social health was significantly below the desirable threshold. The analysis of the dimensions of social health showed that students obtained comparatively higher scores in social integration, while the lowest scores were observed in social coherence, indicating an unfavorable status in this dimension. These findings highlight the need for targeted interventions to strengthen specific components, particularly social coherence, to promote students’ social health. It is therefore recommended that the university implement structured educational programs, counseling services, and participatory activities aimed at fostering these components and enhancing overall social health among students.